What do ESP practitioners need to know? A reflective article on ESP practitioners’ knowledge base - Moyetta, Daniela; Carpintero, Pablo; Galfioni, Gabriela; Bracamonte, Florencia (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This reflective article explores the critical knowledge base required for English for Specific Purposes (ESP) practitioners to effectively facilitate students’ development of discursive competence within academic and professional contexts. The article discusses the significance of specialised knowledge encompassing disciplinary cultures epistemologies, and genre awareness, arguing that such knowledge is essential for ESP practitioners to navigate and integrate into various professional communities. It also emphasises the importance of interdisciplinary collaboration with subject specialists to enhance course relevance and authenticity. The reflection culminates in advocating for improved teacher training programs that emphasise specialised education for ESP practitioners, promoting continuous professional development and further research in the Argentinean context. By addressing these areas, the article aims to contribute to a deeper understanding of the ESP practitioners’ necessary competencies for fostering students’ engagement in their respective disciplinary cultures.